The effect of Ethyl Methane Sulfonate (EMS) on regeneration and somaclonal variations of Petunia (Petunia hybrida vilm.) - N., Sahi; A.A., Ehsanpour (Penerbit Universiti Kebangsaan Malaysia, 2014)
In order to study the effect of EMS (Ethyl Methane Sulfonate) on plant regeneration of Petunia (Petunia hybrida Vilm.), sterile seeds were cultured in MS medium. Leaf segments from in vitro grown plants were treated with 1% and 2% EMS for 15, 30 and 60 min and were then transferred to plant regeneration medium (MS and BAP, 05 mg/l). No growth was observed in leaf explants treated with 2% EMS for 30 and 60 min. Regenerated shoots from samples treated with 1 or 2% for 15 min were then transferred to MS medium and were sub cultured after rooting. Plants treated with 2% EMS for 15 min showed a significant reduction in the dry and fresh weight. RAPD-PCR analysis using OPAA6 and FPK101 primers showed few differences among treated and untreated plants with EMS.